HUBUNGAN PROGRAM GERAKAN LITERASI SEKOLAH (GLS) DENGAN LITERASI BACA-TULIS SISWA KELAS VIII SMP NEGERI 1 TARAKAN - Apriani, Eva (Universitas Hamzanwadi, 2021)
This study aims to determine the relationship and closeness between the School Literacy Movement Program (GLS) on the Reading and Writing Literacy of Class VIII Students of SMP Negeri 1 Tarakan and the implementation of the GLS Program at SMP Negeri 1 Tarakan. This type of research is descriptive quantitative. The population in the study were all class VIII students of SMP Negeri 1 Tarakan in the 2020/2021 academic year, totaling 345 students. Samples were taken based on the Simple Random Sampling technique. Based on the results of data analysis, 69 of 86 students showed a supportive attitude in the GLS and Literacy and Literacy Program at school and based on the results of Kendall's Tau-B correlation test at a significant level of 5% (N = 86) obtained a p-value of less than 0.05 ( 0.000 < 0.05) means that there is a relationship between the GLS Program and Literacy. Then, the result of Z count is greater than Z table (4,972 > 1.65). This shows that there is a significant and strong relationship between the GLS Program and the Literacy and Literacy of students in schools. Thus, it can be concluded that